ADOPSI PENUH HARMONISASI STANDAR AKUNTANSI - Sugiarti Sugiarti (Universitas Sahid Surakarta, 2016)
Accounting standard can be compared and can be required by multinational company. Accounting standard useful for users of financial statements who want evaluate the financial statements of companies with a global reach. The problems faced them are (Media Akuntansi, 2005a) : About a translation problem itself, IFRS who published into English language needs to be translated, discrepancy between IFRS with national law, because in some countries accounting standards included as part of the national law, the structure and complexity of international standards, with the IFRS raises concerns that the standard will be thick and complex. Indo-nesian responseto the IFRS standards in the field of profession, IAI supports the harmonization of accounting standards through the adoption and adaptation of AIS. Indonesian financial accounting standards need to adopt IFRS as the need forfinancial information that can be recognized globally to be competitive and attract investors global. Existence harmonization even convergence to IFRS accounting information, it is expected to have major quality is the main relevansi. The quality of comparability and indispensable for facilitate comparisons between countries and financial reports for decision making. Adoption benefits include saving time andmoney, to protect the interests of society, economic expansion progresses rap-idly tothe same standards, the financial statements will be the same in all countries.